2012
DOI: 10.1002/psc.1434
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of anticancer heptapeptides containing a unique lipophilic β2,2‐amino acid building block

Abstract: We report a series of synthetic anticancer heptapeptides (H-KKWβ(2,2) WKK-NH(2)) containing eight different central lipophilic β(2,2) -amino acid building blocks, which have demonstrated high efficiency when used as scaffolds in small cationic antimicrobial peptides and peptidomimetics. The most potent peptides in the present study had IC(50) values of 9-23 µm against human Burkitt's lymphoma and murine B-cell lymphoma and were all nonhaemolytic (EC(50) > 200 µm). The most promising peptide 10e also demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Especially heptapeptides containing β 2,2 ‐amino acids with two 2‐naphthyl‐methylene or para ‐CF 3 ‐benzyl side chains were highly potent against cancer cells and displayed low toxicity against non‐malignant cells (side chain structures are shown in Scheme ). The central lipophilic β 2,2 ‐amino acid is believed to induce turns in peptides, and our studies have shown that the β 2,2 ‐amino acid also protects against proteolytic degradation by trypsin and α ‐chymotrypsin .…”
Section: Introductionmentioning
confidence: 83%
“…Especially heptapeptides containing β 2,2 ‐amino acids with two 2‐naphthyl‐methylene or para ‐CF 3 ‐benzyl side chains were highly potent against cancer cells and displayed low toxicity against non‐malignant cells (side chain structures are shown in Scheme ). The central lipophilic β 2,2 ‐amino acid is believed to induce turns in peptides, and our studies have shown that the β 2,2 ‐amino acid also protects against proteolytic degradation by trypsin and α ‐chymotrypsin .…”
Section: Introductionmentioning
confidence: 83%
“…Serum stability might be improved by the incorporation of D-amino acids on the peptide sequence (Riedl et al, 2011b) and by cyclization of the structures (Torfoss et al, 2012b). The incorporation of lipophilic β 2, 2 amino acids building blocks into heptapeptides resulted in a potent anticancer activity toward human and murine lymphoma cells, as well as high proteolytic stability and low toxicity against non-tumor cells (Torfoss et al, 2012a,b). The authors of this study state that the incorporation of the disubstituted β 2, 2 amino acids in an α-helical peptide added an extra methylene group to the structure which in combination with two bulky lipophilic substituents, increased stability to protein degradation.…”
Section: Perspectives and Open Questions On Anticancer Peptides Desigmentioning
confidence: 99%
“…The authors of this study state that the incorporation of the disubstituted β 2, 2 amino acids in an α-helical peptide added an extra methylene group to the structure which in combination with two bulky lipophilic substituents, increased stability to protein degradation. Indeed, the central β 2, 2 amino acid is flanked by two tryptophan residues to increase bulkiness and forming a lipophilic sequence where lysine cationic residues, are located at the N- and C-terminals (Torfoss et al, 2012a). The cyclization of these peptides resulted in structures with increased rigidity, amphipathicity and with changes in the secondary structure conformation which lead to an improvement of the anticancer potency against human lymphoma cells (Torfoss et al, 2012b).…”
Section: Perspectives and Open Questions On Anticancer Peptides Desigmentioning
confidence: 99%
“…This may be due to challenging developmental processes for turning these peptides into potent pharmaceutical drugs (e.g. cost of synthesis, peptide size, charge, and solubility) (Tørfoss et al, 2012[88]). However, with the increase in ACP research, more peptides may reach clinical trials in the future.…”
Section: Anticancer Peptidesmentioning
confidence: 99%